Localization of aurora A and aurora B kinases during interphase: role of the N-terminal domain - Rannou, Yoann (Landes Bioscience, 2008)
Aurora kinases possess a conserved catalytic domain (CD) and a N-terminal domain (ND) that varies in size and sequence. We have previously reported that the N-terminal domain of AuroraA (AurA) participates in the localization of the kinase to the centrosome in interphase. AuroraB (AurB) is a chromosome passenger protein and its N-terminal domain is not necessary for its localization or function during mitosis. Using various combinations of GFP-AurA and AurB protein domains we show that in interphase, AurB N-terminal domain is required for nuclear localization in Xenopus XL2 cells. In human cells, however, we found both AurA and AurB kinases in the nucleus, AurA being mainly cytoplasmic and AurB mainly nuclear. Both proteins are actively excluded from the nucleus by a CRM1 dependent pathway. Interestingly, at a functional level, in interphase, every combination of Aurora kinase domains (ND-CD) rescues histone H3 Serine10 phosphorylation defect induced by AurB knockdown. This clearly indicates the presence of a functional AurA in the nucleus. Additionally, the chimera ND-AurA/CD-AurB was much more efficient than the ND-AurB/CD-AurA to rescue multinucleation also induced by AurB knockdown. This indicates that the catalytic domain of AurB is required to fulfill specific functions during mitosis that cannot be fulfilled by the catalytic domain of AurA, probably for localization reasons during mitosis.